Regional Characteristics of Atmospheric Sulfate Formation in East Antarctica Imprinted on 17O‐Excess Signature. Issue 6 (15th March 2021) - Ishino, S.; Hattori, S.; Legrand, M.; Chen, Q.; Alexander, B.; Shao, J.; Huang, J.; Jaeglé, L.; Jourdain, B.; Preunkert, S.; Yamada, A.; Yoshida, N.; et al.
Abstract: 17 O‐excess ( Δ 17 O =  δ 17 O − 0.52 × δ 18 O) of sulfate trapped in Antarctic ice cores has been proposed as a potential tool for assessing past oxidant chemistry, while insufficient understanding of atmospheric sulfate formation around Antarctica hampers its interpretation. To probe influences of regional specific chemistry, we compared year‐round observations of Δ 17 O of non‐sea‐salt sulfate in aerosols ( Δ 17 O(SO4 2− )nss ) at Dome C and Dumont d'Urville, inland and coastal sites in East Antarctica, throughout the year 2011. Although Δ 17 O(SO4 2− )nss at both sites showed consistent seasonality with summer minima (∼1.0‰) and winter maxima (∼2.5‰) owing to sunlight‐driven changes in the relative importance of O3 oxidation to OH and H2 O2 oxidation, significant intersite differences were observed in austral spring–summer and autumn. The cooccurrence of higher Δ 17 O(SO4 2− )nss at inland (2.0‰ ± 0.1‰) than the coastal site (1.2‰ ± 0.1‰) and chemical destruction of methanesulfonate (MS – ) in aerosols at inland during spring–summer (October–December), combined with the first estimated Δ 17 O(MS – ) of ∼16‰, implies that MS – destruction produces sulfate with high Δ 17 O(SO4 2− )nss of ∼12‰. If contributing to the known postdepositional decrease of MS – in snow, this process should also cause a significant postdepositional increase in Δ 17 O(SO4 2− )nss over 1‰, that can reconcile the discrepancy between Δ 17 O(SO4 2− )nss in the atmosphere and ice. The higher Δ 17 O(SO4 2− )nss at the coastal site than inland during autumn (March–May) may be associated with oxidation process involving reactive bromine and/or sea‐salt particles around the coastal region. Plain Language Summary: It has been proposed that the past variations of atmospheric oxidants (e.g., ozone) might be estimated using 17 O‐excess, a unique isotopic signature, of sulfate trapped in polar ice cores. However, chemical processes altering 17 O‐excess of sulfate in the atmosphere and also in snow after deposition have not been fully understood, limiting the practicality of the signature. We investigated regional differences in 17 O‐excess of sulfate in aerosol particles at inland and coastal sites in East Antarctica. Our results suggest that the chemical destruction of atmospheric methanesulfonate, the second abundant sulfur compound in Antarctic aerosols, produces sulfate with significantly high 17 O‐excess signature at inland Antarctica. If also occurring in snow, this process can explain the existing gap of the signature between the atmosphere and ice. These results should be taken into account through future studies investigating the past atmospheric compositions using this signature in ice cores. Key Points: Regional characteristics of atmospheric sulfate formation were probed by 17 O‐excess ( Δ 17 O) of sulfate at inland and coastal East Antarctica Specifically, high Δ 17 O in spring–summer at inland suggests that chemical destruction of methanesulfonate (MS – ) on the Antarctic Plateau produces sulfate Existing gap between Δ 17 O of sulfate in the atmosphere and ice can be reconciled by MS – destruction in snow